Mazowszanie w protestanckim Elblągu w okresie nowożytnym - Zawadzki, Wojciech (Saeculum Christianum. Pismo Historyczne, 2019)
In modern times, Royal Prussia used to be a multi-denominational and multicultural area. Elbląg, one of the three great Prussian cities, had a similar character until 1772. Since the middle of the 16th century, many Poles from Lithuania and the Crown, including Mazovia, came to this Lutheran town. The preserved Catholic metric books and the matricules of the academic gymnasium established in 1535 in Elbląg allow a study of the presence of the Mazovians in Elbląg in the past. In the source material, apart from the personal data, also the place of origin, age and sometimes family and social status were recorded. In total, 66 newcomers from Mazovia were registered in the archives of Elbląg. They did not play any significant role in the history of the city.